Dzieło sztuki w teorii restauracji Cesare Brandiego - Krawczyk, Janusz (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2011)
This article contains a discussion on the Cesare Brandi’s views on the issue of coming into existence, the reception and the restoration of the works of art. Also, the concept of the creative process suggested by Brandi in the publications like Carmine o della pittura (1945), Arcadio o della scultura, Eliante o dell’architecttura (1956) and Celso o della poesia (1957), and the ref lection on the specific determinants of the being of the work of art and its perception in the act of the consciousness, developed by him in the later studies, are compared. Within the latter thread, the concepts suggested by Brandi in Teoria del restauro (1963) and Le due vie (1966) are analysed. A special attention is given to the anti-positivist aspects of the discussed theory: the consequences of the accepting of the phenomenological definition of the matter of the work of art are revealed, the concept of the aesthetic instance and the historic instance of the consciousness are discussed, and the premises taken into account by Brandi when he acknowledged conservation as the action ancillary to restauration are characterized.